Tracking Self-Efficacy And Career Readiness Of Junior High: Adoptive Career Development Plan - Margarito Balag Callao; Jeffrey C. Lacson (Elementary Education Online, 2023)
This research tracked the self-efficacy and career readiness of grade 10 students of Toledo City Division during the school year 2017-2018 as a basis for a proposed adoptive career development plan. The study used the cumulative method and questionnaire as the main tool in gathering data. The socio-demographic profile of the learners such as age, gender, birth order, combined family income, parents’ highest educational attainment, the occupational field of interest and perception on a career helping profession, and self-efficacy and career readiness were the factors considered affecting learners’ career inclination. Students’ profiles for socio-demographic profile and standardized questionnaire for self-concept and career readiness were answered through Google form by the 2604 grade 10 students from the 12 Public National High Schools of Toledo City Division. Among the identified profile, self-efficacy and career readiness to the learners’ career interest, self-efficacy, and career readiness were found out to be the influencing variables that affected the grade 10 in their career choice. Toledo City Division career helping professionals should create an adaptive career career guidance program among the grade 10 students that would formally introduce them to the senior high school program. Implement activities for personal development, career exploration, career decision, and career options purposes. It is recommended that the proposed development plan for grade 10 be adopted.